Effects of large dams on the aquatic food web along a coastal stream with high sediment loads - Roussel, Jean-Marc; Fraisse, Stéphane; Dézerald, Olivier; Fovet, Ophélie; Pannard, Alexandrine; Rodriguez-Perez, Hector; Crave, Alain; Gorzerino, Caroline; Poupelin, Maxime; Forget, Guillaume; Huteau, Dominique; Thomas, Alban; et al. (Frontiers in Ecology and Evolution, 2024)
The contribution of two basal energy sourcesdetrital organic matter and primary producersas part of aquatic food webs varies typically along river continua. A host of barriers to river flow increase the water residence time and sediment and nutrient retention in reservoirs worldwide, and potentially alter the balance between detritus-based and algae-based energy pathways in the downstream food webs.We explored this issue on the Sélune River (Normandy, France), a small coastal stream that drains an agricultural catchment with high sediment runoff. Seasonal measurements of the following parameters were compared upstream and downstream of the reservoirs of two large dams (16 m and 36 m high): sediment fluxes, nutrient and chlorophyll a concentrations, algal communities in the epilithic biofilm (taxonomic composition, biomass and growth), and benthic invertebrate communities (abundance and trophic guild structure). As anticipated, annual sediment fluxes were much lower downstream of the reservoirs, where significant decreases in water turbidity, phosphate and silicate concentrations were recorded. A higher chlorophyll a concentration in water and a higher contribution of pelagic algae taxa to the photosynthetic biofilm suggested drifting and deposition of reservoir-borne phytoplankton downriver. Photosynthetic biofilm growth was higher downstream of the reservoirs in spring and fall, and so was the abundance of herbivores in the invertebrate community, notably scrapers and algae eaters. Energy pathways within riverine food webs were traced using stable isotope analyses of carbon (C) and nitrogen in the tissues of aquatic consumers (invertebrates and fish). Mixing models revealed a discontinuity in the origin of the C entering the food webs along the river continuum, confirming a greater contribution of algal C to aquatic consumers downstream of the reservoirs. These results illustrate mechanisms whereby large reservoirs can modulate C flow in food webs along a small coastal river with high sediment loads, and make it possible to anticipate the effects of dam removal on the future river ecosystem.